Up your business! : 7 steps to fix, build or stretch your organization - Anderson, Dave, 1961- (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2007)
Praise for the first edition of Up Your Business!. ''Dave Anderson has hit another home run! Up Your Business! is an invaluable, highly readable guide that should be on the desk--and in the mind--of anyone demanding top-level performance from themselves and others.
Always remember, "it's the people, stupid" -- Abolish corporate welfare : create a culture of merit -- Develop your human capital : how to train, coach, mentor, and retain eagles -- Its all right to aim high if you have plenty of ammo -- Look in the mirror : executing your leadership twelve-pack -- Survive success : how to overcome the six temptations of successful organizations -- Build long-term vitality : steps for execution and follow-through -- Close the gap between knowing and doing.
Includes bibliographical references and index.
Previous edition: 2003.
Print version record.
John Wiley and Sons
Keywords: Organizational change; Organizational Innovation; Changement organisationnel; BUSINESS & ECONOMICS -- Structural Adjustment; Organizational change